Education of Waste Cooking Oil Processing into Aromatherapy Candles for 2 Junior High School Karanganyar Students - Arbianti, Arbianti; Mutiarra Ridyo Arum; Agung Prasetyo; Norbertus Citra Irawan; Teguh Supriyadi; Wiyono (Journal of Community Capacity Empowerment, 2024)
Waste is a complex problem and an important challenge for the sustainable development of a circular economy and can have social, environmental and economic impacts. This service aims to provide education to students so that students can have high knowledge and awareness of waste processing and can utilize used cooking oil waste to make aromatherapy candles. This service was carried out at 2 Junior High School Karanganyar on Thursday, June 20 2024. The service method was socialization and direct practice in making aromatherapy candles. Students have the skills and are successful in making aromatherapy candles according to the material presented by the speaker. This activity succeeded in increasing students' awareness and knowledge regarding household waste management. Students showed high enthusiasm in following the process of processing used cooking oil waste into useful products such as aromatherapy candles, while also expressing their creativity in this process. Positive support from teachers also contributed to the successful implementation of this waste treatment.